Root-induced Changes in the Rhizosphere of Extreme High Yield Tropical Rice: 1. Soil Chemical Properties - Erry Purnomo; Maman Turjaman; Anna Hairani; Athaillah Mursyid; Dodik Choiron; Raina Yulia; Mitsuru Osaki (JOURNAL OF TROPICAL SOILS, 2010)
Root-induced Changes in the Rhizosphere of Extreme High Yield Tropical Rice: 1. Soil Chemical Properties     (E Purnomo,  M Turjaman, A Hairani, A Mursyid, D Choiron, R Yulia and M Osaki): Padi Panjang cultivar is one of many local rice cultivars found in South Kalimantan that yields 8 Mg ha-1 without fertilizer after last transplanting. The mechanisms involved in sustaining nutrient supply to sustain the extreme high yield are of interest. The following work aims to investigate the changes of soil chemical properties in rizhosphere of Padi Panjang cultivar. The Padi Panjang cultivar was grown in a rhizobox filled with soils from 3 different villages in Banjar Regency, South Kalimantan Province, namely, Kuin, Bunipah and Guntung Papuyu. The rice plant was grown for 5 weeks. At the end of the growing period, soil chemical properties such as pH, aluminum (Al), phosphorus (P), potassium (K+), ammonium (NH4+), and nitrate (NO3-) were measured. The results showed that Padi Panjang cultivar had the capability to change the soil chemical properties in the rhizophere. The impact was more extent compared with IR64 cultivar. The changes were depended on soil character, especially, soil texture. The soil from Guntung Papuyu was the least affected by root. It was observed that Padi Panjang cultivar acidified more than IR64. A depletion zone of K+ and NH4+ was found in the rhizosphere of both Padi Panjang and IR64 cultivars. The depletion zone of these ions could reach as far as 3 cm from the rhizosphere. For P, the depletion zone only occurred in the rhizosphere soil of IR64 cultivar. However, for Padi Panjang cultivar, the depletion zone of P did not exist. The Padi Panjang cultivar was able to maintain P concentration the same as or higher than control soil without plant. This is the first report showing that Padi Panjang cultivar can be considered as efficient lowland rice cultivar in absorbing not only P but also K in a P- and K-deficient-soil.